Software networks: virtualization, SDN, 5G and security - Pujolle, Guy (London, United Kingdom : ISTE Ltd, 2015)
Currently, networking technology is experiencing its third major wave of revolution. The first was the move from circuit-switched mode to packet-switched mode, and the second from hardwired to wireless mode.
Virtualization -- SDN (Software-Defined Networking) -- Smart Edges -- New-Generation Protocols -- Mobile Cloud Networking and Mobility Control -- Wi-Fi and 5G -- Security -- Concretization and Morphware Networks.
Includes bibliographical references and index.
Keywords: CLOUD COMOPUTING